Marketing Strategy of Umrah Travel Agent and Religious Attitude in Indonesia - Nurohman, Dede; Sari, Nadia Roosmalita; Himmati, Risdiana; Mas'ud, Riduan (International Journal of Scientific Research and Management (IJSRM), 2023)
Religious tourism has become a trend nowadays. In Indonesia, religious tourism is dominated by Hajj and Umrah departures. Every year, the increasing demand for Hajj and Umrah services makes Hajj and Umrah travel agents emerge, both legal and illegal, and compete. Several strategies are implemented to capture this huge market opportunity. This has implications for the blurring of the spiritual dimension of worship itself. This paper reveals how the religious travel industry influences society and its impact on people's religious attitude. This study explores data through in-depth interviews with travel agency managers, KBIHU (Hajj & Umrah Guidance Group), and pilgrims and conducting document studies from these institutions in direct written form or through electronic media. This study finds that the travel agents’ ways of business in attracting the pilgrims are through internal strategies such as package and price variations, and also by external methods to establish partnerships with KBIHU, individual agents, and public figures. Practical implications and Originality/value-These ways of business impact the religious attitude of Muslims, which are consumptive and profane. This research results can be used as material for evaluating the implementation of Hajj and Umrah trips, both by the government, travel agencies, and prospective pilgrims. This is a pioneer empirical study that focuses on religious tourism and religious attitude of Indonesian muslims.